Genome-wide transcriptional analysis of silica nanoparticle-induced toxicity in zebrafish embryos. Issue 2 (2nd February 2016) - Hu, Hejing; Li, Qiuling; Jiang, Lizhen; Zou, Yang; Duan, Junchao; Sun, Zhiwei
Graphical Abstract: Abstract: Although silica nanoparticles (SiNPs) have a promising application in biomedical fields, there is still a lack of comprehensive understanding of genome-wide transcriptional analysis. This study aims to clarify the toxic effect and molecular mechanisms of SiNPs in zebrafish embryos based on microarray analysis and bioinformatics analysis. Microarray data analysis demonstrated that SiNP-induced toxicity in zebrafish embryos affected expression of 2515 genes, including 1107 genes that were up-regulated and 1408 genes that were down-regulated. These differentially expressed genes were subjected to bioinformatics analysis for exploring the biological processes triggered by SiNPs in zebrafish embryos. Gene ontology analysis showed that SiNPs caused significant changes in gene expression patterns related to many important functions, including response to stimuli, immune response, cellular processes, and embryonic development. In addition, pathway analysis and Signal-net analysis indicated that the gap junction, vascular smooth muscle contraction, and metabolic pathways, apoptosis, the MAPK signaling pathway, the calcium signaling pathway and the JAK-STAT signaling pathway were the most prominent significant pathways in SiNP-induced toxicity in zebrafish embryos. In addition, the results from qRT-PCR and western blot analysis showed that the IL-6 dependent JAK1/STAT3 signaling pathway was activated by SiNPs in zebrafish embryos. In summary, our data will provide compelling clues for further exploration of SiNP-induced toxicity in zebrafish embryos.